Gambling on Europe: David Cameron and the 2016 referendum. Issue 1 (April 2018) - Smith, Julie
Abstract Membership of the European Union has divided British political parties for decades. On taking office, David Cameron hoped to move his Conservative Party beyond the electorally rather unwelcome focus on 'Europe'. By 2013, he felt the best way to resolve the divisions in his own party was to try to renegotiate the UK's membership of the EU and hold a referendum on continuing membership. This article argues that the gamble was Cameron's to lose but that a combination of poor judgement and ill-timing on his part alongside the more potent message of the Leave campaign contributed to precisely the outcome Cameron did not want: he lost office; the country looked set to the leave the EU; and the divisions within his party were far from healed.